Study of Dental Caries and PTH Gene - Reis, Caio Luiz Bitencourt; Barbosa, Mariane Carolina Faria; de Lima, Daniela Coelho; Madalena, Isabela Ribeiro; Baratto-Filho, Flares; Proff, Peter; de Oliveira, Daniela Silva Barroso; Paddenberg, Eva; Küchler, Erika Calvano; Kirschneck, Christian (Frontiers in Dental Medicine, 2021)
Parathyroid hormone (PTH) is essential for calcium and phosphate homeostasis in odontogenesis-related cells. Therefore, the present study aimed to investigate the association between single nucleotide polymorphisms in the gene encoding PTH, and dental caries in Brazilian children. Three hundred and fifty-three children (170 boys and 183 girls, age ranging from 8 to 11 years old) were included in this study. The International System for Detection and Assessment of Carious Lesions (ICDAS) was used for diagnosis of dental caries. Visible biofilm was also evaluated during the clinical examination. Genomic DNA was extracted from saliva for real-time PCR to evaluate the single nucleotide polymorphisms rs6256, rs307247 and rs694 in PTH gene. Dental caries was classified in ICDAS0 vs. ICDAS1−6 or ICDAS1−2 vs. ICDAS3−6. Chi-square test, binary logistic regression adjusted by biofilm and haplotype analyses were performed (p < 0.05). Biofilm was associated with dental caries (p < 0.05). There were no associations between dental caries and rs6256, rs307247, rs694 in none of the analyses performed (p > 0.05). In conclusion, the present study supports that the single nucleotide polymorphisms rs6256, rs307247, and rs694 in the PTH-encoding gene are not associated with dental caries in Brazilian children.